Indicators of environmental loading and sustainability of urban systems. An emergy-based environmental footprint. (November 2018) - Viglia, Silvio; Civitillo, Dario Felice; Cacciapuoti, Gianluca; Ulgiati, Sergio
Abstract: Cities are the engine of economic development and human wellbeing, but their dynamics needs to be supported by the convergence of large flows of material and energy resources. Assessing a city resource metabolism becomes increasingly crucial, not only concerning the relation with the environment as a source or a sink, but also concerning the internal dynamics of resource exchange among city components and sectors. We applied Emergy Accounting (EMA) and Cumulative Energy Demand (CED) methods to develop and validate indicators of urban environmental sustainability, using as case studies five urban systems of different size in Italy. CED allowed an assessment of the commercial energy consumption required on local and global scales to support the city life and economy. Airborne emissions related to direct and indirect energy consumption were also assessed. EMA was used to quantify the environmental support required for the urban metabolism, in terms of resource generation and ecosystem services supply. Combining these three aspects, a new metric is discussed and developed to estimate the environmental impact of cities, with reference to their resource use, in order to implement comprehensive indicators and suggest resource use criteria at urban level. A city's support area to buffer upstream and downstream environmental loading is also calculated. Relative and absolute sustainability concepts are introduced and discussed, showing how far the investigated cities are from a resource-based environmentally sustainable state. Finally, practices are suggested as an exit strategy from the present intensive fossil powered economy towards a higher level of environmental sustainability and wellbeing.